Mind gym : an athlete's guide to inner excellence - Mack, Gary; Casstevens, David (McGraw Hill-Ascent Audio, 2002)
Praise for Mind Gym "Believing in yourself is paramount to success for any athlete. Gary's lessons and David's writing provide examples of the importance of the mental game." --Ben Crenshaw, two-time Masters champion and former Ryder Cup captain "Mind Gym hits a home run. If you want to build mental muscle for the major leagues, read this book." --Ken Griffey Jr., Major League Baseball MVP "I read Mind Gym on my way to the Sydney Olympics and really got a lot out of it. Gary has important lessons to teach, and you'll find the exercises fun and beneficial." --Jason Kidd, NBA All-Star and Olympic gold-medal winner "I love the book Mind Gym." --Madison Kocian, 2016 U.S. Women's Gymnastics Team, 2015 Uneven Bars World Champion, as told to Us Weekly In Mind Gym, noted sports psychology consultant Gary Mack explains how your mind influences your performance on the field or on the court as much as your physical skill does, if not more so. Through forty accessible lessons and inspirational anecdotes from prominent athletes--many of whom he has worked with--you will learn the same techniques and exercises Mack uses to help elite athletes build mental "muscle." Mind Gym will give you the "head edge" over the competition.